Essential business skills for social work managers : tools for optimizing programs and organizations - Germak, Andrew J. (New York : Routledge, 2015)
"Many social workers find themselves in management positions within a few years of graduating from MSW programs. Most of these jobs are in nonprofit human service organizations in which, increasingly, business acumen is necessary to maintain grants and donations, start new programs, market services to clients, supervise the finance function, and understand the external environment.This book teaches MSW students and early-stage social work management practitioners the essential business skills needed to manage programs and organizations; to improve their overall management toolkit for finding a better job or getting promoted; and, ultimately, to gain parity with other managers holding MBA degrees and working in the human service space. This text can serve as a desk reference for managers to troubleshoot various situations. It is also appropriate for social work macro practice courses at the undergraduate and graduate levels, as well as courses that cover human resource management and financial management."--
Includes bibliographical references and index.
Keywords: Social work administration; Management; SOCIAL SCIENCE / Social Work; SOCIAL SCIENCE / Sociology / General; BUSINESS & ECONOMICS / General; Management; Social work administration